2011
DOI: 10.1080/07315724.2011.10719960
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Placebo-Controlled Trial of Guava Juice as a Source of Ascorbic Acid to Reduce Iron Deficiency in Tarahumara Indigenous Schoolchildren of Northern Mexico

Abstract: Guava juice providing 200 mg AA at one meal on each school day had a marginal effect on Hb and PF concentrations in children consuming high-phytate diets fortified with iron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 51 publications
1
15
0
2
Order By: Relevance
“…Intakes of ascorbic acid in the form of guava and other locally grown seasonal fruit have been shown to be high among nonanemic Tanzanian schoolchildren aged 7-12 y on the basis of FFQs (52). A recent study reported that the consumption of guava juice showed only marginal beneficial effects on hemoglobin and ferritin concentrations in iron-deficient anemic children (53). Our results are in agreement with the above literature.…”
Section: Discussionsupporting
confidence: 92%
“…Intakes of ascorbic acid in the form of guava and other locally grown seasonal fruit have been shown to be high among nonanemic Tanzanian schoolchildren aged 7-12 y on the basis of FFQs (52). A recent study reported that the consumption of guava juice showed only marginal beneficial effects on hemoglobin and ferritin concentrations in iron-deficient anemic children (53). Our results are in agreement with the above literature.…”
Section: Discussionsupporting
confidence: 92%
“…The effect of vitamin C from natural dietary sources on the iron status is not widely covered in the literature and previous papers have limitations in study design, including intervention dose, sample size, or subject category . In addition, there are no studies (as far as we are aware) testing the impact of long‐term regular consumption of vitamin C–rich fruits with a supplementary nutrition meal program on preschoolers.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we considered an intercluster correlation of 0.01 ( n = 10 in each AWC), 95% confidence interval, 80% power, and 20% attrition to achieve the required sample size. Earlier studies reported a change in hemoglobin (Hb) by 0.4–1.0 g/dL with a sample size ranging from n = 89 to 95. In the present study, a subsample of 80 per group was computed for assessing the impact of the intervention on iron biomarkers based on changes in hemoglobin (Hb) of 0.8 g/dL and a standard deviation of 1.5 g/dL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Mexico, en experiment of the provision of guava juice containing of 200 mg AA led to an increase in levels of 0.64 mg/dl. 7 In Indonesia, guava juice research has been carried out to increase Hemoglobin levels and the results show an increase in Hemoglobin levels. 8,9 This study aims to assess the effect of the provision of guava juice containing AA of 200mg/100 grams and Fe tablets 2 times a day on the increase in hemoglobin levels in third trimester pregnant women..…”
mentioning
confidence: 99%